Theatricality: The Specificity of Theatrical Language - Feral, Josette (MiKAN, 2006)
The concept of "theatricality" appears in many and widelydiffering disciplines - theatre, anthropology, sociology, psychology, management, economics, politics, psychoanalysis, to name but afew. In these the concept is expressed either metaphorically or as ananalytical tool, in various and sometimes even contradictory ways. Moreover, outside the field of theatre, this concept appears to bereturning us to its widespread linguistic use; but precisely where is itreturning us to? This is the question discussed here. The article aimsto bring the nature of theatre itself into focus against a background ofindividual theatrical practices, theories of stage-play and aesthetics.It attempts to delineate those parameters shared by all theatricalenterprises from time immemorial. Despite the vast scope of such anenterprise, its pertinence requires at least a first step in the directionof arriving at such a definition. This article is such a step, seeking toestablish points of reference for subsequent reflection.